Expression of Human Epidermal Growth Factor Receptor-2 in Resected Rectal Cancer. Issue 47 (November 2015) - Meng, Xiangjiao; Huang, Zhaoqin; Di, Jian; Mu, Dianbin; Wang, Yawei; Zhao, Xianguang; Zhao, Hanxi; Zhu, Wanqi; Li, Xiaolin; Kong, Lingling; Xing, Ligang
Abstract : Abstract: The addition of trastuzumab to chemotherapy was demonstrated to be beneficial for advanced human epidermal growth factor receptor-2 (HER-2) positive gastric cancer. However, the HER-2 status of rectal cancer remains uncertain. This study aimed to determine the HER-2 expression in a large multicenter cohort of rectal cancer patients. The clinical and pathological features of 717 patients were retrospectively reviewed. All the patients were diagnosed with primary rectal adenocarcinoma without distant metastasis and took surgery directly without any preoperative anticancer treatment. HER-2 status was assessed on resected samples. A total of 99 cases with IHC3+ and 16 cases with IHC 2+ plus gene amplification were determined as HER-2 positive. 22.6% of HER-2 positive patients had local recurrence, whereas 16.9% of HER-2 negative patients did ( P = 0.146). HER-2 positive tumors were more likely to have distant metastasis ( P = 0.007). Univariate analysis revealed that pathological tumor stage, pathological node stage, positive margin, and lymphovascular invasion were significantly correlated with 5-year disease-free survival (DFS) and 5-year overall survival (OS). The patients with >10 dissected lymph nodes showed significantly longer OS ( P = 0.045) but not DFS ( P = 0.054). HER-2 negative patients had significantly better 5-year DFS ( P < 0.001) and 5-year OS ( P = 0.013) than those of the HER-2 positive patients. In the subgroup analysis for the early rectal cancer and locally advanced rectal cancer, HER-2 was also a poor predictor for survival. Multivariate analysis revealed that HER-2 was an independent prognostic factor for 5-year DFS (hazard ratio [HR] = 1.919, 95% confidence interval [CI] 1.415–2.605, P < 0.001) and for 5-year OS (HR = 1.549, 95% CI 1.097–2.186, P = 0.013). When the treatment was included in the analysis for locally advanced patients, HER-2 was a prognostic factor for 5-year DFS ( P = 0.001) but not for 5-year OS ( P = 0.106). This study confirmed that HER-2 was expressed in a part of patients with rectal cancers and might be used as a negative predictor. The results may support the trials to assess the efficacy of trastuzumab in treating HER-2 positive rectal cancer patients.